2017
DOI: 10.1007/s10776-017-0341-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of LoRa LPWAN Technology for Indoor Remote Health and Wellbeing Monitoring

Abstract: Abstract. Long lifetime of a wireless sensor/actuator node, low transceiver chip cost and large coverage area are the main characteristics of the low power wide area network (LPWAN) technologies. These targets correlate well with the requirements imposed by the health and wellbeing applications of the digital age. Therefore, LPWANs can found their niche among traditional short range technologies for wireless body area networks, such as ZigBee, Bluetooth and ultra wideband. To check this hypothesis, in this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 12 publications
4
74
0
2
Order By: Relevance
“…We find that the greater the bandwidth is, the lower PRR it achieves. This result corresponds well with the results in [24]. This is because the symbol rate R s = BW 2 SF ; therefore, when the transmission power is constant, the wider the bandwidth is, the less energy will be distributed for each symbol.…”
Section: Coverage Experiments Resultssupporting
confidence: 89%
“…We find that the greater the bandwidth is, the lower PRR it achieves. This result corresponds well with the results in [24]. This is because the symbol rate R s = BW 2 SF ; therefore, when the transmission power is constant, the wider the bandwidth is, the less energy will be distributed for each symbol.…”
Section: Coverage Experiments Resultssupporting
confidence: 89%
“…As shown in Figure 12, the test results showed that the received signal strength decreased with the increase of communication distance, and the packet loss rate was increasing, which was consistent with other scholars' test and evaluation of LoRa wireless communication technology performance [34,41], although a different application environment will have different effects on link quality and packet loss rate. From the test results, the wireless sensor network based on LoRa technology can realize the reliability of communication in the harsh climate of the brine mining field and meet the practical application requirements.…”
Section: Reliability Test Of Communication Linksupporting
confidence: 81%
“…By inviting corporate managers and operators to participate in the system evaluation, we discussed the system performance and formed a consensus on how to develop the system to improve the efficiency of salt lake brine production management [42]. Test scenario 3: Reliability test of communication link based on LoRa and GPRS The reliability of wireless links from sensor nodes to the server is evaluated by measuring the packet loss rate of the LoRa network within 30 days at the brine mines [41]. First, the sensor node transmits a 20-byte packet with a fixed transmission power of 15 dBm at a transmission interval of 60 s. Then, the GPRS gateway forwards data received from the sensor node to the server.…”
Section: System Assessment Resultsmentioning
confidence: 99%
“…A single gateway can serve tens of thousands of low power wireless end devices [5]. Thus indoors one cell can cover a large real-estate [6] and outdoors coverage area can be tens of kilometers [5].…”
Section: Lora Wide Area Networkmentioning
confidence: 99%